1999
DOI: 10.1097/00005131-199908000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Plate Osteosynthesis: Does Percutaneous Plating Disrupt Femoral Blood Supply Less Than the Traditional Technique?

Abstract: A percutaneous minimally invasive plating technique disrupts the femoral blood supply less than the traditional open method. Such minimally invasive methods may be more advantageous biologically than the traditional method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
134
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(149 citation statements)
references
References 16 publications
5
134
0
8
Order By: Relevance
“…To avoid these complications, the hybrid or circular wire external fixator is a good option, but problems of nonunion, mal-union, and pin track infections are common. (Marsh et al 1995) Recently, the MIPO technique has been developed-not only to improve the rate of fracture healing (Krettek et al 1997, Collinge et al 2000, but also to limit soft tissue elevation at the fracture site (Farouk et al 1999). In our series, all fractures united without primary or secondary bone graft, as has been reported for distal tibial metaphyseal fractures (Oh et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid these complications, the hybrid or circular wire external fixator is a good option, but problems of nonunion, mal-union, and pin track infections are common. (Marsh et al 1995) Recently, the MIPO technique has been developed-not only to improve the rate of fracture healing (Krettek et al 1997, Collinge et al 2000, but also to limit soft tissue elevation at the fracture site (Farouk et al 1999). In our series, all fractures united without primary or secondary bone graft, as has been reported for distal tibial metaphyseal fractures (Oh et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study of Siebenrock et al, [31] the nonunion rate was 7% with biological method and 16% with traditional method. Farouk and Krettek [46] conducted a study on fresh human cadavers and found that percutaneous minimal invasive plating technique disrupts the femoral blood supply less than the traditional open method.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive plate osteosynthesis (MIPO), in addition, avoids disturbance of the injury zone altogether [4,5,8,15]. Major bone fragments usually retain muscular attachment and, if they are not stabilised, they continue flipping by contraction of the attached muscles, interfering with the union.…”
Section: Primary Plate Fixation Of Multifragmentary Fracturesmentioning
confidence: 99%
“…Prolongation of the healing time of fractures has a deleterious effect on the patient's limb, body, socioeconomic and psychological status. Better understanding of the mechanics of fracture stabilisation and of the biological requirements of fracture healing has improved the outcome in these difficult cases [3,4].…”
Section: Introductionmentioning
confidence: 99%